Metabolic profiling of chickpea-Fusarium interaction identifies differential modulation of disease resistance pathways - Kumar, Yashwant; Dholakia, Bhushan B.; Panigrahi, Priyabrata; Kadoo, Narendra Y.; Giri, Ashok P.; Gupta, Vidya S. (Phytochemistry, 2015)
Chickpea is the third most widely grown legume in the world and mainly used as a vegetarian source of human dietary protein. Fusarium wilt, caused by Fusarium oxysporum f. sp. ciceri (Foc), is one of the major threats to global chickpea production. Host resistance is the best way to protect crops from diseases; however, in spite of using various approaches, the mechanism of Foc resistance in chickpea remains largely obscure. In the present study, non-targeted metabolic profiling at several time points of resistant and susceptible chickpea cultivars using high-resolution liquid chromatography-mass spectrometry was applied to better understand the mechanistic basis of wilt resistance or susceptibility. Multivariate analysis of the data (OPLS-DA) revealed discriminating metabolites in chickpea root tissue after Foc inoculation such as flavonoids, isoflavonoids, alkaloids, amino acids and sugars. Foc inoculated resistant plants had more flavonoids and isoflavonoids along with their malonyl conjugates. Many antifungal metabolites that were induced after Foc infection viz, aurantion-obstine beta-glucosides and querecitin were elevated in resistant cultivar. Overall, diverse genetic and biochemical mechanisms were operational in the resistant cultivar for Foc defense as compared to the susceptible plant. The resistant chickpea plants employed the above-mentioned metabolic pathways as potential defense strategy against Foc. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chickpea; Fusarium wilt; LC-MS; Metabolomics; OPLS-DA; Phytoalexin